Pattern of Non-Communicable Diseases among the Admitted Patients in a District Level Hospital of Bangladesh (Bangladesh Heart Journal, 2019)
Background: Non-communicable Diseases (NCD), particularly cardiovascular diseases, cancer, diabetes and chronic respiratory disease, have emerged as the leading threat to mankind worldwide. Likewise in Bangladesh, an increasing trend of incidence of NCDs has been observed and already they have become major public health concern. Hence, we aimed to study the pattern of NCDs among the admitted patients at an Upazila Health Complex (UHC) in Bangladesh.Methods: In this retrospective study, data of in-hospital patients admitted from January 2018 to June 2018 in UHC, Chhagalnaiya, Feni was analyzed. Data on age, gender, occupation, hospital admission/discharge and diagnosis of disease was obtained from the hospital register. Diseases were categorized into NCD or communicable disease using the World Health Organization’s International Classification of Diseases (ICD) coding system.Results: 1,367 adult patients with different diseases were admitted into the medical ward over the study period of six months (mean age 57.4 ± 17.9 years; 61.3% male and 38.7% female). There were 904 cases of various NCDs constituting 66.1% of total admissions. The number of cases of NCDs was two times more compared to CDs (ratio 2:1). In all six months, admissions due to NCDs were significantly higher compared to communicable diseases CDs (p = 0.0001). Among the admissions due to NCDs, more than half (51.3%) were aged between 50 to 69 years. In terms of pattern of disease, cardiovascular diseases were the number one cause for hospital admission followed by endocrine disorders.Conclusion: This study found that the burden of NCDs has increased among the admitted patients in an UHC. These findings could be useful to draw the attention of health authorities to adopt preventive strategies against NCDs even at Upazila level.Bangladesh Heart Journal 2019; 34(2) : 118-121